Abnormal agency experiences in schizophrenia patients: Examining the role of psychotic symptoms and familial risk. (April 2017) - Prikken, Merel; van der Weiden, Anouk; Renes, Robert A.; Koevoets, Martijn G.J.C.; Heering, Henriette D.; Kahn, René S.; Aarts, Henk; van Haren, Neeltje E.M.
Abstract: Experiencing self-agency over one's own action outcomes is essential for social functioning. Recent research revealed that patients with schizophrenia do not use implicitly available information about their action-outcomes (i.e., prime-based agency inference) to arrive at self-agency experiences. Here, we examined whether this is related to symptoms and/or familial risk to develop the disease. Fifty-four patients, 54 controls, and 19 unaffected (and unrelated) siblings performed an agency inference task, in which experienced agency was measured over action-outcomes that matched or mismatched outcome-primes that were presented before action performance. The Positive and Negative Syndrome Scale (PANSS) and Comprehensive Assessment of Symptoms and History (CASH) were administered to assess psychopathology. Impairments in prime-based inferences did not differ between patients with symptoms of over- and underattribution. However, patients with agency underattribution symptoms reported significantly lower overall self-agency experiences. Siblings displayed stronger prime-based agency inferences than patients, but weaker prime-based inferences than healthy controls. However, these differences were not statistically significant. Findings suggest that impairments in prime-based agency inferences may be a trait characteristic of schizophrenia. Moreover, this study may stimulate further research on the familial basis and the clinical relevance of impairments in implicit agency inferences. Highlights: Patients with symptoms of underattribution show lower agency ratings. Prime-based agency inferences are impaired in patients, irrespective of symptoms. Healthy siblings might be vulnerable to deficits in prime-based agency processing. Impairments in prime-based agency processing might be a trait characteristic.